2020
DOI: 10.1016/j.celrep.2020.108331
|View full text |Cite|
|
Sign up to set email alerts
|

Airway Microbiota-Host Interactions Regulate Secretory Leukocyte Protease Inhibitor Levels and Influence Allergic Airway Inflammation

Abstract: SUMMARY Homeostatic mucosal immune responses are fine-tuned by naturally evolved interactions with native microbes, and integrating these relationships into experimental models can provide new insights into human diseases. Here, we leverage a murine-adapted airway microbe, Bordetella pseudohinzii ( Bph ), to investigate how chronic colonization impacts mucosal immunity and the development of allergic airway inflammation (AAI). Colonization with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 80 publications
1
28
2
Order By: Relevance
“…Our in-depth profiling of a single dyad revealed an ETBF+ microbiome from a donor with asthma increased the Th17 response and oxidative stress within the lungs of humanized gnotobiotic mice in the context of AAI. While previous studies have implicated airway microbes in inducing Th17 responses in AAI (24, 66), our work provides evidence that this phenotype can be mediated by a gut microbiota-expressed factor. In follow-up monocolonization experiments, we confirmed that the ETBF isolated from the donor with asthma causes increased gut barrier permeability and pulmonary oxidative stress in the context of pre-existing inflammation.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Our in-depth profiling of a single dyad revealed an ETBF+ microbiome from a donor with asthma increased the Th17 response and oxidative stress within the lungs of humanized gnotobiotic mice in the context of AAI. While previous studies have implicated airway microbes in inducing Th17 responses in AAI (24, 66), our work provides evidence that this phenotype can be mediated by a gut microbiota-expressed factor. In follow-up monocolonization experiments, we confirmed that the ETBF isolated from the donor with asthma causes increased gut barrier permeability and pulmonary oxidative stress in the context of pre-existing inflammation.…”
Section: Discussioncontrasting
confidence: 40%
“…To investigate if asthma is associated with distinct gut microbial signatures outside of early childhood, we recruited 17 adults and 19 school-aged children with physician-diagnosed, moderate-to-severe atopic asthma along with 40 adult and 19 school-aged healthy controls into the previously described Microbiome and Asthma Research Study (24) (MARS; see demographic summary in Supplemental Table 1; see also Methods). We performed V4-16S rRNA amplicon sequencing of participant stool samples obtained at the patient’s baseline and identified amplicon sequence variants (ASVs) using DADA2 (25) (Supplemental Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that this mutant strain was uniquely susceptible to T cell-mediated protection and that PsxA likely contributes to the ability of B. pseudohinzii to evade T cell mediated clearance. This resistance to T cell action is consistent with the ability of B. pseudohinzii to suppress a Th17-mediated allergic response in an asthma model (Jaeger et al, 2020). In addition, these effects are also consistent with published observations on the interactions between PTx from B. pertussis and T lymphocytes as well as other published PTx-like toxins, including inhibition of migration and cytokine signaling (Cyster and Goodnow, 1995;Schneider et al, 2009;Brink et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, we noted that AEA treatment increased the expression of mBD2, which was associated with decreased Pseudomonas in the SEB + AEA group when compared to SEB + VEH group. Similarly, LYZ2, another AMP which was induced by AEA has been shown to play a key role in killing bacteria in the lungs and preventing the spread of the infection [ 56 , 57 ]. Additionally, S24_7 (Muribaculaceae) which is a beneficial bacteria [ 58 , 59 ], was seen in the SEB + AEA group in both the gut and the lungs, suggesting that there may be crosstalk between gut and lung microbiomes.…”
Section: Discussionmentioning
confidence: 99%